Factors associated with fractures in HIV-infected persons: which factors matter?. Issue 1 (January 2017) - Gedmintas, L.; Wright, E.; Dong, Y.; Lehmann, E.; Katz, J.; Solomon, D.; Losina, E.
Abstract Summary This study aims to determine what factors are associated with increased risk of fracture among patients with HIV, in particular whether an important medication used to treat HIV, tenofovir, is associated with fracture. Our study found that while co-infection with hepatitis C and markers of HIV severity were associated with fracture, tenofovir was not. Introduction Growing evidence suggests that tenofovir disoproxil fumarate decreases bone density among patients with HIV, but there are conflicting reports as to whether this decrease in bone density translates to higher fracture risk. We aimed to determine what factors were associated with an increased risk of fracture for patients with HIV, in particular whether tenofovir is associated with elevated fracture risk. Methods We conducted a retrospective cohort study at two tertiary care hospitals in Boston, MA, between 2001 and 2012 to determine whether tenofovir use is associated with elevated all-site fracture risk, as compared to other antiretroviral medications. We also examined other potential factors associated with fracture among patients with HIV. Results We identified 1981 HIV-infected patients who had at some point used tenofovir and 682 patients who had not. The mean age was 43 years, and 72 % were male. The hepatitis C co-infection rate was 28 %, about 40 % had nadir CD4 count <200, and about 40 % had a history of an AIDS-defining illness. We did not find an association between risk of fracture and tenofovir disoproxil fumarate (TDF) (adjusted RR (aRR) 0.8, 95 % CI 0.6–1.1). However, co-infection with hepatitis C did increase risk of fracture (aRR 1.6, 95 % CI 1.1–2.3), as did nadir CD4 count <200 (aRR 3.1, 95 % CI 1.9–5.0) and history of AIDS-defining illness (aRR 1.6, 95 % CI 1.1–2.2). Conclusion There was no association found between fracture and tenofovir use, but there were associations between co-infection with hepatitis C and markers of advanced HIV disease and fracture.